Exposure of grapes to smoke of vegetation with varying lignin composition and accretion of lignin derived putative smoke taint compounds in wine - Kelly, David; Zerihun, Ayalsew; Singh, D.; Vitzthun von Eckstaedt, Christiane; Gibberd, Mark; Grice, Kliti; Downey, M. (Elsevier, 2012)
Smoke taint in wines from bushfire smoke exposure has become a concern for wine producers. Smoke taint compounds are primarily derived from pyrolysis of the lignin component of fuels. This work examined the influence of the lignin composition of pyrolysed vegetation on the types of putative smoke taint compounds that accrue in wines. At véraison, Merlot vines were exposed to smoke generated from five vegetation types with differing lignin composition. Smoke was generated under pyrolysis conditions that simulated bushfire temperature profiles. Lignin and smoke composition of each fuel type along with putative smoke taint compounds in wines were determined. The results showed that, regardless of fuel type, the commonly reported guaiacyl lignin derived smoke taint compounds, guaiacol and 4-methylguaiacol, represented about 20% of the total phenols in wines. Quantitatively, syringyl lignin derived compounds dominated the total phenol pools in both free and bound forms. The contributions of p-hydroxyphenyls were generally similar to the guaiacyl sources. A further unexpected outcome of the study was that pine smoke affected wines had significantly elevated levels of syringols compared to the controls although pine fuel and its smoke emission lacked syringyl products.